(untitled) - Clements, Matthew (New York, 2004)
This book has been written as a practical guide for finance markets professionals to explain US monetary policy and to make forecasts of future interest rate levels. Aimed at market players, familiar with US policy instruments, Explaining and Forecasting the US Federal Funds Rate will provide a means of making independent interest rate forecasts as well as explaining current rate levels.
Keywords: Monetary policy,Interest rates,Federal funds market (United States); United States,United States